Waits for Surgery Following Hip Fracture - Kira Leeb, Kathleen Morris, Linda Choy and Tracy Johnson (Healthcare Policy, 2006)
Almost all hip fracture patients undergo surgery to repair the fracture. Recent research suggests that timely repair is important for good outcomes following surgery. Patients who had surgical repair of a hip fracture in 2003-2004 were identified using hospitalization data collected by the Canadian Institute for Health Information. Time to surgery was calculated from day of admission to day of surgery. The associations of both patient and system characteristics with waits for surgery were considered. While the majority of patients had surgery on the day of or the day following admission, 29% waited two days or longer for surgery. Wait times were related to patients' age, hospital size, day of admission and whether patients were transferred. [To view the French abstract, please scroll down.]